Optimization of Nanoemulsion Formula Containing Erythromycin with VCO and Varying Concentrations of Tween-80 and PEG-400 - Mardiyanto; Mohadi, Risfidian; Fithri, Najma Annuria; Kurniawan, Gilang (Science and Technology Indonesia, 2024)
Erythromycin, a macrolide antibiotic is classified into Biopharmaceutical Classification System (BCS) class II which has low solubility in water. The low solubility corresponds to the bioavailability in the blood. One strategy to increase the solubility of Erythromycin is the formulation of erythromycin in nanoemulsion. This research aims to form nanoemulsion using the PIT (Phase Transition Temperature) method for obtaining the optimum formula of erythromycin nanoemulsion using virgin coconut oil (VCO) can be found with varying concentrations of Tween 80 surfactant and PEG 400 cosurfactant. The selection of the optimum formula was assisted by Design Expert software with the Factorial design method 22. The basis for determining the optimum formula is based on the results of organoleptic characterization tests, adsorption efficiency (%EE), percent transmittance, viscosity test, pH test, and stability test. The optimum formula was nanoemulsion which had a concentration of Tween 80 25% and PEG 400 25% as a desirability value of <1. The results of the optimum formula showed that the particle size was 170.6±12.8594 nm, polydispersity index (PDI) 0.403±0.04406, and zeta potential -8.8667±0.25697 mV and had an appropriate stability without phase separation during stability test.